KONSEP DIRI PELAKU GAY DI KOTA PEKANBARU - Reza Fahlevi; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Gay are identified as people who have an interest in psychological and emotional terms, especially towards men who are commonly called s. Besides that, Gay also have biological needs like humans in general. Factors that cause someone to be , namely the condition of an incomplete family will have a negative impact on personality development, social development, and emotional development. This also results in adolescents experiencing adjustment difficulties in the form of behavioral problems, learning difficulties, or withdrawal from the social environment and adolescents will feel less attention and affection or even experience stress and trauma from having a relationship with the opposite sex. The purpose of this study is to analyze the self-concept of actors in Pekanbaru City. This type of research is a qualitative research with a phenomenological approach. The subjects that became my research were 5 Gay. Data collection techniques are interviews, observation and documentation while data analysis techniques use qualitative methods. From the results of the research and discussion, it can be concluded that the informant as a person has a positive self-concept and follows their conscience in acting. However, human attitudes and behavior are always looking for reasons to reject their existence and attitudes that cause the emergence of various diseases such as AIDS, venereal diseases, and so on. Keywords: Self-Concept, Actor,